Blitz [videorecording (DVD)] - Lester, Elliott; Statham, Jason, 1967-; Gillen, Aidan, 1968-; Morrissey, David; Considine, Paddy; Ashton, Zawe; Bruen, Ken (Millennium Entertainment, 2011)
A tough cop is dispatched to take down a serial killer who has been targeting police officers. A fast-paced thriller set in contemporary London reflects the challenges faced by a group of police officers working in a modern, multicultural society.